Practical information security management : a complete guide to planning and implementation / Tony Campbell - Campbell, Tony
This book provides a wealth of practical advice for anyone responsible for information security management in the workplace. Focusing on the 'how' rather than the 'what', Practical Information Security Management shows you how to create security-focused business propositions that consider the balance between cost, risk and usability. The book accompanies you on your journey as you set out on the path to become an information security manager, offering a wealth of background history that explains how the industry works today, looking at how you set up an effective infosec practice, hire the right people and strike the balance between security controls, costs and risk. Together we'll cut through the policies, regulations and standards to expose the real inner workings of what make a security management program effective, covering the full gamut of subject matter pertaining to security management: organizational structures, security architectures, technical controls, governance frameworks, and operational security matters. What You Will Learn: The practical aspects of being an effective information security manager How to strike the right balance between cost and risk How to take security policies and standards and make them work in reality How to leverage complex security functions, such as Digital Forensics, Incident Response and Security Architecture Who This Book is For: This is a book for anyone who wants to make a difference in offering effective security management for their business. You might already be a security manager seeking insight into areas of the job that you've not looked at before, or you might be a techie or risk guy wanting to switch into this challenging new career. Whatever your career goals are, Practical Information Security Management has something to offer you.